Pemanfaatan Bambu Lokal pada Desain Cottage Umah Pitu Ruang, Aceh Tengah - Shadrina Aliyya Shafa; Pratitou Arafat; Ferian Yavis Pradika; Elysa Wulandari (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Central Aceh Regency possesses a rich vernacular architectural heritage represented by Umah Pitu Ruang, a traditional house that reflects the cultural identity of the Gayo community. However, its application in contemporary tourism architecture remains limited. This study examines the architectural transformation of Umah Pitu Ruang in the design of the Bamboo Umah Pitu Ruang cottage in Aceh Tengah and explores the use of local bamboo as the primary building material. A descriptive qualitative approach was employed through literature review, conceptual design analysis, field observation, physical measurement of bamboo, and semi-structured interviews.